Strong influence of variants near MC4R on adiposity in children and adults: a cross-sectional study in Indian population - Prakash Dwivedi, Om; Tabassum, Rubina; Chauhan, Ganesh; Kaur, Ismeet; Ghosh, Saurabh; Marwaha, Raman K; Tandon, Nikhil; Bharadwaj, Dwaipayan (Journal of human genetics, 2013)
Common variants near melanocortin 4 receptor (MC4R) gene are shown to be associated with adiposity but have varied effects in different age groups. Among Indians, studies have shown association of these variants with obesity in adults, but their association in children is yet to be confirmed. We evaluated association of rs17782313 and rs12970134 near MC4R with adiposity and related traits in Indians including 1362 children and 4077 adults (consisting of 2049 diabetic and 2028 nondiabetic adult subjects). Both variants rs17782313 and rs12970134 showed strong association with adiposity measures (weight, body mass index and waist circumference) in children (P-range 7.6 × 10(-5)-3.8 × 10(-12)) and nominal association in nondiabetic adults (P-range 0.05-0.003). Effect sizes on adiposity measures in children (β range 0.22-0.26 Z-score) were ~3-fold higher compared with adults (β range 0.06-0.08). The minor alleles of both variants showed borderline association (P-range 0.08-0.04) with risk of type 2 diabetes in adults. Meta-analysis of rs12970134 in >12 000 Indian adults corroborated its association with adiposity (P≤2.2 × 10(-9)), homeostasis model assessment-estimated insulin resistance (P=4.0 × 10(-5)) and type 2 diabetes (P=0.003) with only moderate heterogeneity, suggesting similar effect on adult Indians residing in different geographical regions. In conclusion, the study demonstrates association of variants near MC4R with obesity and related traits in Indian children and adults, with higher impact during childhood.